2D Graphdiyne: A Rising Star on the Horizon of Energy Conversion. Issue 21 (6th September 2021) - Wang, Zhongqiang; Qi, Lu; Zheng, Zhiqiang; Xue, Yurui; Li, Yuliang
Abstract: Two‐dimensional (2D) graphdiyne (GDY), a rapidly rising star on the horizon of carbon materials, is a new carbon allotrope featuring sp‐ and sp 2 ‐cohybridized carbon atoms and 2D one‐atom‐thick network. Since the first successful synthesis of GDY by Professor Li's group in 2010, GDY has attached great interests from both scientific and industrial viewpoints based on its unique structure and physicochemical properties, which provides a fertile ground for applications in various fields including electrocatalysis, energy conversion, energy storage and optoelectronic devices. In this work, various potential properties of the GDY‐based electrocatalysts and their recent advances in energy conversion are reviewed, including atomic catalysts, heterogeneous catalysts, and metal‐free catalysts. The critical role of GDY in improving catalytic activity and stability is analyzed. The perspectives of the challenges and opportunities faced by GDY‐based materials for energy conversion are also outlined. Abstract : Graphdiyne (GDY), a novel sp/sp 2 ‐cohybridized one‐atom‐thick carbon allotrope, has attracted great interests from various fields such as catalysis and energy conversion, owing to its unusual and unique properties. In this review, we summarized the advances in the development of GDY‐based efficient catalysts including GDY‐based atomic catalysts, heterojunction catalysts and metal‐free catalyst, and their application in efficient energy conversion.